Development of a new high-temperature and high-strength polymer gel for plugging fractured reservoirs - Li, Zhi-yong; Li, Xin-gang; Du, Kun; Liu, Hua-kang (Upstream Oil and Gas Technology, 2020)
In fractured reservoirs, the fracture size distribution is wide with strong heterogeneity, and wide fractures are not easily plugged. Conventional plugging methods have limitations in reservoir leakage problems. The matching degree of plugging materials and reservoir fractures is relatively low once small particles are transported deep into the reservoir, which can finally cause reservoir damage. Gel plays an important role in the temporary plugging of fractured reservoirs. However, there are currently few mature gel systems that can maintain good rheological properties at room temperature, good gelation at a high temperature and a sustained plugging strength. In this paper, a high-temperature and high-strength (HTHS) gel system was developed, and its properties were evaluated in the laboratory. The gel is cross-linked by covalent bonds, and its temperature resistance can reach 150 °C. Rheological and gelation tests show that the gel solution exhibits good rheological properties at room temperature and can cross-link into a gel at high temperatures. The gelation time could be flexibly adjusted from 4 to 10 h. The gel has good expansibility and can entirely fill fractures. The plugging test reveals that the plugging pressure can reach 0.25 MPa/cm in a 5-mm fracture, and the strength stability can be maintained for one month. Gelation stability can be maintained in the presence of formation water and drilling fluid. The gel has a good self-breaking capability after a period of time and does not affect reservoir production. This study can provide a plugging solution for fractured reservoirs at high temperatures and pressures.